Heat transfer analysis and material behaviour of martensitic steel during thermal cycling process - Akdogan, A.; Koyun, A. (TAYLOR & FRANCIS LTD, 2007)
The present paper commits to the study of the heat transfer analysis and material behaviour of the thermally cycled mould steel used in glassware production. Thermal cycling experiments of AISI 431 stainless steel were carried out at specially designed computer controlled cycling mechanism which could contact the sample with molten glass at 900 degrees C. Two different heat transfer analysis models were performed to calculate the temperature distribution in the specimen which was an input into the stress models as thermal loads. There is a consistency between the model results which were acquired assuming that the material was only subjected to plastic deformation, and the measurements that were performed during thermal cycling process by thermocouples. These cycling models could be used for advanced failure analysis of this kind of subjected materials. The results of repeated high temperature cycling process and thermal shocks created by initial temperature domain (20-900 degrees C) are discussed.
Keywords: thermal cycling; glass mould steel; heat transfer analysis; material behaviour; FATIGUE BEHAVIOR; MODEL; Materials Science; Metallurgy & Metallurgical Engineering